A primazia de Wall Street e a continuidade dos privilégios do setor financeiro no Governo Trump: The primacy of Wall Street and the continuity of financial sector privileges on Trump administration - Maia, Eduardo Santos (Conjuntura internacional, 2018)
O presente trabalho abordará a primazia dos interesses de Wall Street no governo Trump. A partir do breve exame do processo de financeirização iniciado na década de 1970, será analisada a relação entre Trump e Wall Street, mormente as iniciativas adotas pelo presidente em favor do setor financeiro. Palavras-chave: Wall Street; governo Trump; desregulação financeira The present paper will address the primacy of Wall Street’s interests in Trump government. Starting from a brief analysis of the process of financialization initiated in the 1970s, the relation between Trump and Wall Street will be analyzed, particularly the initiatives adopted by the president in favor of the financial sector. Key words: Wall Street; Trump government; financial deregulation